Can a Peer Support the Process of Self-Management in Narcolepsy? A Qualitative Narrative Analysis of a Narcoleptic Patient - Franceschini, Christian; Fante, Chiara; Filardi, Marco; Folli, Maria Claudia; Brazzi, Francesca; Pizza, Fabio; D’Anselmo, Anita; Ingravallo, Francesca; Antelmi, Elena; Plazzi, Giuseppe (Frontiers in Psychology, 2020)
IIntroduction: Narcolepsy type 1 (NT1) is a chronic and rare sleep disorder typically arising during adolescence and young adulthood. The main symptoms are excessive daytime sleepiness and cataplexy, a prototypical fall down elicited by huge emotions. Social relationships, school, work and general health perception are frequently impaired in patients, who often show lower quality-of-life scores. We report which management strategies a young patient (DMG) adopted to cope with NT1 during his growth avoiding exhibiting serious impairments to his global functioning. Methods: A clinical psychologist explores the history of the patient’s disease and the self-acquired strategies used to cope with the symptoms. The patient’s global adaptation to the disease, stress-related managing skills, and overall well-being is assessed by standardized scales (Illness Behavior Questionnaire- IBQ; Coping Orientations to Problems Experienced - COPE and Psychological General Well Being Index - PGWBI). We conducted a qualitative analysis of the patient’s narration of his illness according to the procedure of the Grounded Theory. The MAXQDA software program was used to code the verbatim transcript. Results: From the qualitative analysis of the interview, three thematic cores emerge: 1) the disease history; 2) the patient’s friendship with AD, a friend of his age diagnosed with NT1 since childhood; 3) the strategies used to deal with his symptoms before the diagnosis of NT1 and the related treatment. From the psychometric tests, the patient presents good coping strategies in dealing with stressful problems and events, based mainly on acceptance and positive reinterpretation of the stressful situation. Conclusions: This case shows that comparing peers of the same age and suffering from the same illness improves the patient's self-management ability to cope and live well with NT1.